Treatment of tourist safety in Brazil in the Spanish media before the Olympic Games of Rio 2016 - Álvarez de la Torre, Jaime (2017)
Safety is one of the main problems of current tourism worldwide and directly threatening the image of any destination. The media contribute to the formation of this image and provide a perception of security or insecurity. Since the perception of insecurity in Brazil has been one of its main weaknesses, the question arises of how the media influence the formation of the image before a major tourist event. A content analysis on the treatment of tourism security in Brazil was carried out for 16 months prior to the Rio'16 Olympic Games in 1,034 Spanish digital media headlines. It is confirmed an excessively alarmist/sensationalist treatment in tourist topics that are related to the image and the Olympic Games. Although in other tourism areas the news is more flat and descriptive it is noticed that stereotypes of image arise on the occasion of major tourist events.